Comparative cerebroprotective potential of d- and l-carnosine following ischemic stroke in mice - Jain, Saurabh; Kim, Eun Sun; Kim, Donghyun; Burrows, David; De Felice, Milena; Kim, Minyeong; Baek, Seung Hoon; Ali, Ali; Redgrave, Jessica; Doeppner, Thorsten R.; Gardner, Iain; Bae, Ok Nam; et al. (International Journal of Molecular Sciences, 2020)
L-carnosine is an attractive therapeutic agent for acute ischemic stroke based on its robust preclinical cerebroprotective properties and wide therapeutic time window. However, large doses are needed for efficacy because carnosine is rapidly degraded in serum by carnosinases. The need for large doses could be particularly problematic when translating to human studies, as humans have much higher levels of serum carnosinases. We hypothesized that D-carnosine, which is not a substrate for carnosinases, may have a better pharmacological profile and may be more efficacious at lower doses than L-carnosine. To test our hypothesis, we explored the comparative pharmacokinetics and neuroprotective properties of D- and L-carnosine in acute ischaemic stroke in mice. We initially investigated the pharmacokinetics of D- and L-carnosine in serum and brain after intravenous (IV) injection in mice. We then investigated the comparative efficacy of D- and Lcarnosine in a mouse model of transient focal cerebral ischemia followed by in vitro testing against excitotoxicity and free radical generation using primary neuronal cultures. The pharmacokinetics of D- and L-carnosine were similar in serum and brain after IV injection in mice. Both D- and Lcarnosine exhibited similar efficacy against mouse focal cerebral ischemia. In vitro studies in neurons showed protection against excitotoxicity and the accumulation of free radicals. D- and Lcarnosine exhibit similar pharmacokinetics and have similar efficacy against experimental stroke in mice. Since humans have far higher levels of carnosinases, D-carnosine may have more favorable pharmacokinetics in future human studies.
Keywords: Animals; Brain Chemistry; Carnosine; Cells, Cultured; Disease Models, Animal; Humans; Injections, Intravenous; Ischemic Stroke; Male; Mice; Neurons; Neuroprotective Agents; Primary Cell Culture; D- and L-carnosine; Efficacy; MCAO; Neuroprotection; Pharmacokinetics; Stroke